2006
DOI: 10.1002/cbic.200500474
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a Novel Thioesterase is Responsible for Polyketide Chain Release during Biosynthesis of the Polyether Ionophore Monensin

Abstract: Polyether ionophores, such as monensin A, are known to be biosynthesised, like many other antibiotic polyketides, on giant modular polyketide synthases (PKSs), but the intermediates and enzymes involved in the subsequent steps of oxidative cyclisation remain undefined. In particular there has been no agreement on the mechanism and timing of the final polyketide chain release. We now report evidence that MonCII from the monensin biosynthetic gene cluster in Streptomyces cinnamonensis, which was previously thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 51 publications
(69 reference statements)
2
53
0
1
Order By: Relevance
“…Due to the absence of a conventional TE domain within the PKS or a NanE-like thioesterase (22,23), there are three candidates for the requisite thioesterase activity in the salinomycin biosynthesis gene cluster. Genes slnDI and slnDII, encoding discrete type II TEs, display high similarity to monAIX and monAX in the monensin gene cluster (14). The slnDI disruption mutant JCY23 produced salinomycin at a level similar to that of wild-type XM211 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Due to the absence of a conventional TE domain within the PKS or a NanE-like thioesterase (22,23), there are three candidates for the requisite thioesterase activity in the salinomycin biosynthesis gene cluster. Genes slnDI and slnDII, encoding discrete type II TEs, display high similarity to monAIX and monAX in the monensin gene cluster (14). The slnDI disruption mutant JCY23 produced salinomycin at a level similar to that of wild-type XM211 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Recently, several experimental results using discrete TE have strongly indicated that cleavage of polyketide-tethered ACP occurred after polyether formation. [49][50][51] The finding of a TE domain at the Cterminal end of Lsd17 (Fig. 2) is noteworthy, since this suggests that the full-length polyketide is cleaved from the ACP domain, as is usual for polyketide metabolites, before polyether formation.…”
Section: Aromatic Ring Formationmentioning
confidence: 84%
“…One major difficulty in elucidating details of the reaction mechanism for polyether formation in the biosynthesis of monensin-type ionophore antibiotics is the involvement of complex modification reactions such as full-length polyketide transfer to discrete ACP, 17) oxidative cascade cyclization of the polyketide bound to ACP, subsequent hydrolysis of discrete TE, [49][50][51] methylation and hydroxylation. In this report, we have identified the gene cluster of another representative ionophore antibiotic, lasalocid.…”
Section: Resultsmentioning
confidence: 99%
“…[211] Auf Grundlage von TE-Proteinstrukturen schlugen Boddy et al vor, dass hydrophobe Wechselwirkungen zwischen dem Bindungshohlraum und dem Substrat die Substratspezifität lenken und damit die Größe des Makrolactons bestimmen. [214] In den Biosyntheseapparaten der Polyether Nanchangmycin [215,216] und Monensin [217] wurden ungewöhnliche Thioesterasen, die zu linearen Produkten führen, identifiziert. Für die Synthese des makrocyclischen Antibiotikums Lankacidin (89) in Streptomyces rochei wurde ein alternativer Cyclisierungsmechanismus vorgeschlagen (Schema 39).…”
Section: B-verzweigung Durch Michael-additionunclassified